Iontophoresis Transcorneal Delivery Technique for Transepithelial Corneal Collagen Crosslinking With Riboflavin in a Rabbit Model - Cassagne, Myriam; Laurent, Camille; Rodrigues, Magda; Galinier, Anne; Spoerl, Eberhard; Galiacy, Stéphane D.; Soler, Vincent; Fournié, Pierre; Malecaze, François (Investigative ophthalmology & visual science, 2016)
We compared an iontophoresis riboflavin delivery technique for transepithelial corneal collagen crosslinking (I-CXL) with a conventional CXL (C-CXL). We designed three experimental sets using 152 New Zealand rabbits to study riboflavin application by iontophoresis using charged riboflavin solution (Ricrolin+) with a 1-mA current for 5 minutes. The first set was to compare riboflavin concentration measured by HPLC in corneas after iontophoresis or conventional riboflavin application. The second set was to analyze autofluorescence and stromal collagen modification immediately and 14 days after I-CXL or C-CXL, by using nonlinear two-photon microscopy (TP) and second harmonic generation (SHG). In the third set, physical modifications after I-CXL and C-CXL were evaluated by stress-strain measurements and by studying corneal resistance against collagenase digestion. Based on HPLC analysis, we found that iontophoresis allowed riboflavin diffusion with 2-fold less riboflavin concentration than conventional application (936.2 ± 312.5 and 1708 ± 908.3 ng/mL, respectively, P < 0.05). Corneal TP and SHG imaging revealed that I-CXL and C-CXL resulted in a comparable increased anterior and median stromal autofluorescence and collagen packing. The stress at 10% strain showed a similar stiffness of corneas treated by I-CXL or C-CXL (631.9 ± 241.5 and 680.3 ± 216.4 kPa, respectively, P = 0.908). Moreover, we observed an increased resistance against corneal collagenase digestion after I-CXL and C-CXL (61.90% ± 5.28% and 72.21% ± 4.32% of remaining surface, respectively, P = 0.154). This experimental study suggests that I-CXL is a promising alternative methodology for riboflavin delivery in crosslinking treatments, preserving the epithelium.